Sequence dependence of stability and intercalation studies on short synthetic oligoribonucleotide duplexes - Sinclair, Alison (My University, 1986)
A phosphotriester synthesis was used to prepare short oligoribonucleotides for study by variable temperature H-NMR. The duplex = single strand transition was monitored by the associated changes in chemical shift and coupling constant for the ribose base, imino, and anomeric protons. A measurable parameter of stability, the melting temperature (Tm), was extracted from the chemical shift versus temperature data. The sequence dependence of stability was studied for a series of tetramer sequences comprising exclusively guanosine and cytidine residues. These sequences formed perfect duplexes with stabilities: (GGCC)₂ > (GCGC)₂ > (CCGG)₂ ≅ GCCG:CGGC > (CGCG)₂, which led to a ranking of stabilities of nearest neighbour interactions: GC:GC ≥ GG:CC > CG:CG. Study of complementary mixtures of GC-rich trimers in the presence and absence of salt revealed a highly salt dependent self-aggregataion of the G-rich strand. A structure for the GCG aggregate is proposed. Studies of stability and structure of base-base mismatches in GC-rich oligoribonucleotides were performed on six pentaribonucleotides derived from the GC tetramers. Two sequences, CCAGG and GCUGC, formed duplexes of comparable stability, containing AxA and UxU mismatches respectively. The mismatched bases stacked into the duplex. One sequence, GGACC, did not duplex; the others (GGUCC, CCUGG, GCAGC) formed structures not incorporating mismatched base pairs. Mixing experiments on the complementary pentamers (e.g., GGACC:GGUCC) allowed study of the effect of introduction of A•U base pairs on the GC tetramer stability. Interealation of proflavine into the mismatch containing duplexes CCAGG and GCUGC (and their parent duplexes CCGG and GCGC) was studied to compare interealation into mismatch and non mismatch sites. Addition of increasing ratios of proflavine produced a steady increase in Tm and shielding for most protons, but there is no indication of site preference or looping out of mismatched bases. GCUGC tabled a threefold higher Tm increase than GCGC, but the starting Tms are too widely separated to allow direct comparison of binding affinities.
Keywords: Biochemistry; Biochemistry